The Kantian Attempt to Solve the Mind-Body Problem. A Critical Approach - Teruel, Pedro Jesús (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
The mind-body problem is one of the perennial challenges in the history of ideas. Immanuel Kant (1724-1804) tried to solve it through an approach with several modulations –parallel to his intellectual evolution– that brought him into contact with both the later projection of the theoretical issue (the mind brain problem) and its practical side (the immortality question). In this paper I face the Kantian approach to the mind-body problem from a triple perspective: descriptive, appraising and critical.